Carrying capacity of Pangean Reservoir, Pasar Baru Village, Pangean Subdistrict, Kuantan Singingi Regency, Riau Province based on dissolved oxygen - Br Sitorus, Chrisna Heni Nozelina; Dahril, Tengku; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractCarrying capacity is an ability of the aquatic environment to support the life of cultivated organisms. This study aims to determine the carrying capacity for aquaculture based on dissolved oxygen concentration. This research was conducted in July-August 2019 at Pangean Reservoir. Water samples were taken at four stations, namely Station 1 (riverin zone), Station 2 and Station 3 (transition zone) and Station 4 (lacustrine zone). In each station has 2 sampling points, namely surface, 2 Secchi depth which is done once a week. Water quality parameters measured are dissolved oxygen, temperature, pH, brightness, depth, phosphate. The results showed that dissolved oxygen (DO) concentrations ranged from 4.2 to 6.2 mg / L on the surface, at a depth of 2 Secchi ranging from 3.07 to 5.67 mg / L. Water quality parameters support depth ranges from 248-388 cm, brightness ranges from 93-102 cm, temperatures range from 29-31oC, pH 5, Total-P 0,043-0,153 mg/L.. The carrying capacity of Pangean Reservoir based on dissolved oxygen is 3,418 kg / year and the number of floating net cages that can operate is 13 units with a size (4 x 6 x 2) m3. The number of marine cage currently available is 100 units. Based on this research, the number of KJA plot units in Pauh Pangean Reservoir has exceeded its carrying capacity.Keyword:Carrying capacity, dissolved oxygen, floating cage, Pangean Reservoir and Water Quality